ANALYSIS OF OPERATING EXPENSES BUDGET AS A COST CONTROL TOOL IN COMPANIES - Halimah Nasution; Henny Andriyani Wirananda; Wilda Sri Munawaroh Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2026)
The operating expense budget is a crucial component of a company's financial planning and control. A well-prepared budget can assist management in controlling operational costs, ensuring efficient and effective company operations. This study aims to analyze the role of the operating expense budget as a tool for controlling company operational costs and identify the obstacles encountered in its implementation. The research method used is qualitative descriptive research with a literature review approach. The results indicate that the operating expense budget plays a significant role in helping management plan, control, and evaluate the company's operational performance. However, budget effectiveness is still influenced by the accuracy of planning, management commitment, and the company's ability to conduct ongoing monitoring and evaluation.